Determinants of ZIS (Zakat, Infaq, and Sadaqah) Participation Preferences among Residents of Bogor Regency (Case Study: BAZNAS Bogor Regency) - Nurdiansyah; Siti Aisyah (Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of literacy, service quality, and ease of access on the interest in paying Zakat, Infaq, and Sedekah (ZIS). The analysis model used is descriptive quantitative, with primary data collected through questionnaires distributed to 190 respondents from the Bogor Regency community. The testing stages included validity, reliability, normality, multicollinearity, heteroscedasticity, coefficient of determination hypothesis testing, and multiple linear regression using E-views version 12. The results of this study indicate that literacy, service quality, and ease of access significantly influence the interest of the Bogor community in paying Zakat, Infaq, and Sedekah (ZIS) at the National Zakat Agency (BAZNAS) in Bogor Regency. Literacy, service quality, and ease of access collectively significantly influence the interest of the Bogor community in paying Zakat, Infaq, and Sedekah (ZIS).